Advances of Metal and Metal Oxide Nanocomposites Synthesis, Characterization and Biomedical Applications - Basavegowda, Nagaraj; Baek, Kwang-Hyun (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Metal and metal oxide nanocomposites have received considerable attention as an alternative to conventional antimicrobial agents because of their diverse shape, size, high surface-to-volume ratio, chemical/physical stability, activity, and a greater degree of selectivity. The design and synthesis of metal and metal oxide nanocomposites (e.g. mono, bi-, tri-, and multi-metallic nanocomposites), as well as polymer-based nanocomposites and hydrogels with diversified nanostructures (e.g. nanoarrays, nanotubes, core-shell, nanosheets, and nanorods), has sparked considerable interest in terms of biomedical therapeutics, bioimaging, biosensors, drug delivery, and antimicrobial attributes.